Constructivist approaches in the teaching-learning process Final Years of Elementary School from the analysis of the Political Pedagogical Project (Research, Society and Development, 2021)
This research aimed to identify if the educational actions for the teaching-learning process, provided in the Political Pedagogical Project (PPP) of a municipal school in the city of Rio Verde-Go, are based on the constructivist approach. It is part of the Postgraduate Program in Teacher Training and Educational Practices of the Instituto Federal Goiano, Rio Verde Campus. To do so, it was conducted by the following question: Which educational actions for teaching-learning outlined in the PPP are signs of a constructivist approach? The methodological procedure used was document analysis. The initial results indicate that in the PPP there are traces of a constructivist approach translated by the incentive to work with teaching projects and by the incentive to the student as the protagonist in the construction of his learning. However, in the document, there is no clarity about which theoretical and methodological elements of constructivism support the teaching practices of teachers and the pedagogical proposal in general.